Kajian Sifat Inovasi Komponen Teknologi untuk Menentukan Pola Diseminasi Pengelolaan Tanaman Terpadu Padi Sawah - Erythrina ,; Rita Indrasti; Agus Muharam (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACT Assessment on Properties of Innovation Technology Component to Determine Dissemination Pattern of Rice Integrated Crop Management (ICM). ICM Field School is one of the strategic programs of the Ministry of Agriculture aimed at accelerating increased production of major food commodities, included rice. This study aims to determine the variability of quantitative trait ICM technology innovation and determine the pattern of technology innovation dissemination of efficient and effective on site-specific conditions based on quantitative and qualitative variability. The data was collected through interviews with 180 farmers in West Java and Central Java. The analysis revealed that six ICM components technology is quite difficult to be adopted are: (1) application of organic matter, (2) legowo crop establishment, (3) fertilization based on crop needs and soil nutrient status, (4) IPM approach to pest control, (5) intermittent irrigation, and (6) weeding with the hedgehog / gasrok. Therefore, dissemination patterns for each category can not follow a linear pattern of the conventional approach, from source technologies - extension – farmer. An understanding of the processes leading to the adoption of new technologies by small-scale farmers has been important to the planning and implementation of successful dissemination and extension programs. Key words: ICM, nature of innovation, dissemination pattern, rice ABSTRAK Sekolah Lapang Pengeloaan Tanaman Terpadu merupakan salah satu program strategis Kementerian Pertanian bertujuan mempercepat peningkatan produksi komoditas pangan utama, termasuk padi. Kajian ini bertujuan untuk mengetahui keragaan sifat inovasi komponen teknologi PTT padi sawah dan menentukan pola diseminasi inovasi teknologi yang efisien dan efektif. Pengumpulan data dilakukan melalui wawancara terhadap 180 petani di Jawa Barat dan Jawa Tengah. Hasil analisis menunjukkan enam komponen teknologi PTT tergolong sulit diadopsi oleh petani yaitu : (1) pemberian bahan organik, (2) sistem tanam legowo, (3) pemupukan berdasarkan kebutuhan tanaman dan status hara tanah, (4) pengendalian OPT dengan pendekatan pengendalian hama terpadu (PHT), (5) irigasi berselang, dan (6) penyiangan dengan landak/gasrok. Oleh karena itu, pola diseminasi untuk setiap kategori tidak bisa mengikuti pola pendekatan konvensional secara linear yaitu dari sumber teknologi ke penyuluh, kemudian ke petani. Pemahaman tentang proses menuju adopsi teknologi baru oleh petani skala kecil di setiap lokasi menjadi penting untuk perencanaan dan pelaksanaan diseminasi dan program penyuluhan inovasi baru spesifik lokasi. Kata kunci: PTT, sifat inovasi, pola diseminasi, padi sawah